為什麼侵入性腦機介面技術是危險的: Why Invasive Brain-Computer Interface Technology is Dangerous - ZHAI, Zhenming (International Journal of Chinese & Comparative Philosophy of Medicine, 2023)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 我們反對侵入性腦機介面應用於人類，主要原因是，我們還幾乎不知道人的意識產生的機制，侵入性腦機介面技術有可能抹掉人的意識；除此之外，應用介面的人很容易被外人控制，失去自由。總之，它違反了以下三條“非對稱原則”：1. 從客體到主體這個方向，資訊越通暢越好，控制信號阻滯度越高越好。2. 從主體到客體這個方向，控制信號越暢通越好，資訊密封度越高越好。3. 以上兩條的鬆動調節，以最嚴苛的程式保證以各個主體為主導。作為人機介面的代替方案，我們開以採用作為“擴展心智＂的互聯網和電腦來實行。傳統上，道家哲學按其義理也為反對侵入性腦機介面技術提供了支援。 People oppose the application of invasive brain–computer interfaces to humans, mainly because they still know little about the mechanism by which human consciousness is generated and such technology could erase human consciousness. In addition, people using brain–computer interfaces can easily be controlled by outsiders and lose their freedom. In other words, brain–computer interfaces violate the following three asymmetry principles. (1) From the object to the subject, the smoother the information flow, the better, and the higher the degree of control signal blockage, the better. (2) From the subject to the object, the smoother the control signal flow, the better, and the higher the degree of information sealing, the better. (3) The relaxation of the above two principles should be carried out using the most stringent procedure to ensure that each subject takes the lead. As a substitute for brain–computer interfaces, we can use the Internet and computers as a kind of “extended mind.” The principles of traditional Taoist philosophy also support opposition to invasive brain–computer interfaces.